Cerebellar disruptions and neurodevelopmental disabilities. Issue 5 (October 2016) - Bosemani, Thangamadhan; Poretti, Andrea
Summary: The vulnerability of the cerebellum during prenatal life to disruptive events such as hemorrhage and infection leads to a wide variety of morphological abnormalities. This review discusses various prenatal cerebellar disruptions including cerebellar agenesis, unilateral cerebellar hypoplasia, cerebellar cleft, global cerebellar hypoplasia, and vanishing cerebellum in Chiari type II malformation. For each entity, we discuss the definition, potential pathomechanism, clinical findings including neurocognitive and behavioral problems, neuroimaging features, and management. Accurate recognition of cerebellar disruptions and their differentiation from malformations is important in terms of diagnosis, prognosis, and genetic counselling.